Perceived causes of cancer in a rural community of Ethiopia: a qualitative study - Tilhahun, Abigiya; Gizaw, Muluken; Abebe, Lidya Genene; Teka, Brhanu; Kaufmann, Andreas; Abbäbä, Tamrat; McMahon-Rössle, Shannon A.; Addissie, Adamu; Kantelhardt, Eva Johanna (Global health action, 2024)
Although cancer incidence and mortality are rising in Ethiopia, lay and health professional perceptions of the disease remain limited. To explore perceptions of cancer, including its causes, signs and symptoms, and transmission within a rural community in Ethiopia. We conducted a qualitative study in four rural neighbourhoods of Butajira in central Ethiopia. Seven Focus Group Discussions (FGDs) and six In-Depth Interviews (IDIs) were held with community members, women representatives, religious leaders and key informants using two interview guides (divided by method). Behaviour change theories and a community research framework were used to summarize the findings. Across respondent categories and data collection methods, respondents described cancer or nekersa, which translates as ‘an illness that cannot be cured’, as serious and fatal. Cancer was further viewed as becoming more common and as underpinning more deaths particularly among women. Causes of cancer largely focused on individual behaviours namely mitch (referring to exposure to sunlight), poor personal hygiene and urinating on the ground/dirty areas. Almost all participants strongly related cancer to a wound that does not heal and entails a foul-smelling discharge. Bleeding and weight loss were other commonly mentioned complaints of cancer. Although cancer is known among rural communities in this area, misconceptions about cancer aetiology and conflation of the signs and symptoms of cancer versus other diseases merit health messaging. Our study calls for design research to determine how to culturally tailor educational materials and deliver health campaigns regarding cancer causes, signs and symptoms within this context. Main findings: Despite efforts to enhance cancer awareness and understanding among rural residents in Ethiopia, various misconceptions persist regarding its causes, transmission and prevention measures.Added knowledge: Unfavourable community perceptions, such as viewing cancer as a death sentence and believing in scientifically unfounded causes and modes of transmission, can significantly impede efforts for cancer prevention and control.Global health impact for policy and action: Effective global health action and policy must start from the local understanding of the terminologies and the perceived cause of the disease to design all-inclusive cancer prevention and control strategies. Main findings: Despite efforts to enhance cancer awareness and understanding among rural residents in Ethiopia, various misconceptions persist regarding its causes, transmission and prevention measures. Added knowledge: Unfavourable community perceptions, such as viewing cancer as a death sentence and believing in scientifically unfounded causes and modes of transmission, can significantly impede efforts for cancer prevention and control. Global health impact for policy and action: Effective global health action and policy must start from the local understanding of the terminologies and the perceived cause of the disease to design all-inclusive cancer prevention and control strategies.
Gesehen am 06.03.2025